2017
DOI: 10.1080/17483107.2017.1290701
|View full text |Cite
|
Sign up to set email alerts
|

How nursing home residents with dementia respond to the interactive art installation ‘VENSTER’: a pilot study

Abstract: The goal of this study was (1) to determine whether and how nursing home residents with dementia respond to the interactive art installation in general and (2) to identify whether responses change when the content type and, therefore, the nature of the interaction with the artwork changes. The interactive art installation 'VENSTER' evokes responses in nursing home residents with dementia, illustrating the potential of interactive artworks in the nursing home environment. Frequently observed responses were nami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 9 publications
0
24
0
5
Order By: Relevance
“…Musical memory is relatively spared in dementia [39] and multiple technology projects have leveraged this including the one-button radio [40], simple music-making interface [41] and collaborative music making [42]. Enjoying art has also led to programmes such as House of Memories 1 , an interactive art installation for care homes [43], making art as an enjoyable pastime [44] and a more focused art therapy programme [45, 46]. …”
Section: Introductionmentioning
confidence: 99%
“…Musical memory is relatively spared in dementia [39] and multiple technology projects have leveraged this including the one-button radio [40], simple music-making interface [41] and collaborative music making [42]. Enjoying art has also led to programmes such as House of Memories 1 , an interactive art installation for care homes [43], making art as an enjoyable pastime [44] and a more focused art therapy programme [45, 46]. …”
Section: Introductionmentioning
confidence: 99%
“…Similar to behavioral interventions, alternative care interventions are typically single component interventions [45,86], targeting PWDs in the moderate to severe stages of the illness process [66,86] living in nursing home or long-term care facilities [10,87]. However, differing from behavioral interventions, the research to date on alternative care interventions have typically lacked aspects of rigorous methodological designs including low sample sizes and lack of an appropriate control group for comparison.…”
Section: Alternative Care Interventionsmentioning
confidence: 99%
“…Although these results provide a starting point, more methodologically rigorous research is needed in order to conclude that these types of intervention programs positively impact behaviors experienced by PWDs and their caregivers. These methodological issues can be seen within other studies which conclude findings based on results that are from caregivers or staff stating their personal experiences in noticing differences within individuals rather than results that are based on statistically significant findings [84,87]. There are, however, a few noted exceptions of alternative care interventions that have employed a randomized control trial design and have found sufficient efficacy.…”
Section: Alternative Care Interventionsmentioning
confidence: 99%
“…Musical memory is relatively spared in dementia [39] and multiple technology projects have leveraged this including the one-button radio [40], simple music-making interface [41] and collaborative music making [42]. Enjoying art has also led to programmes such as House of Memories 1 , an interactive art installation for care homes [43], making art as an enjoyable pastime [44] and a more focused art therapy programme [45,46].…”
Section: Leisure and Activitiesmentioning
confidence: 99%